Developmental changes in audio-visual speech integration during the first year of life in infants at elevated and typical likelihood of autism - Elena Capelli; Maddalena Irma Cassa; Elena Maria Riboldi; Carolina Beretta; Eleonora Siri; Chiara Cantiani; Massimo Molteni; Valentina Riva (PLoS ONE, 2026)
Infants’ ability to integrate auditory and visual information, i.e., audiovisual integration (AVI), emerges during the first year and is crucial for effective communication and early development. However, there is limited longitudinal research on how AVI develops across the first year of life, particularly in infants at elevated likelihood of autism (EL). This study aimed to investigate the developmental trajectories of AVI in response to congruent and incongruent speech stimuli in EL and typical likelihood (TL) infants at 6, 9, and 12 months. Using eye-tracking techniques and the McGurk effect paradigm, we explored infants’ preferential looking behavior towards facial features (eyes vs. mouth) and their response to audiovisual congruence. EL infants were then evaluated at 24 months to explore the associations between AVI and later autism-related traits. Across likelihood groups, infants showed a robust developmental shift from greater attention to the eyes at 6 months toward increased attention to the mouth at 9 and 12 months, consistent with expected developmental changes in audiovisual speech processing. Infants also displayed higher mouth preference in the non-fusible mismatch condition at 6 months, suggesting early sensitivity to audiovisual incongruence. Interestingly, EL infants showed a delayed developmental shift toward mouth-looking across the first year of life. Exploratory outcome analyses revealed that infants showing clinical signs of autism at 24 months displayed a flatter developmental trajectory in eyes-to-mouth preference. The present study emphasizes the importance of examining sensory processing trajectories in EL infants, as delayed shifts in attention to the mouth could signal subtle developmental differences that may have long-term implications for subsequent communication skills.